Pemphigoid gestationis successfully treated with intravenous immunoglobulin. (7th April 2018) - Almeida, Filipa Tavares; Sarabando, Rita; Pardal, Joana; Brito, Celeste
Abstract : Pemphigoid gestationis (PG), also known as herpes gestationis, is a rare autoimmune blistering disease specific to pregnancy, which usually presents in the second or third trimesters and, in 15%–25% of cases, during the immediate postpartum period. 1 Although the ethiopathogeny of PG is not fully clarified, most patients develop antibodies against a 180 kDa transmembrane hemidesmosomal protein (BP180; BPAG2; collagen XVII). 2 PG has a strong association with human leucocyte antigens DR3 and DR4. 3 We report a case of a 29-year-old female patient with PG successfully treated with intravenous immunoglobulin.